Platelet Rich Plasma and Hyaluronic Acid Blend for the Treatment of Osteoarthritis: Rheological and Biological Evaluation - Russo, Fabrizio; D’Este, Matteo; Vadalà, Gianluca; Cattani, Caterina; Papalia, Rocco; Alini, Mauro; Denaro, Vincenzo (PloS one, 2016)
Osteoarthritis (OA) is the most common musculoskeletal disease. Current treatments for OA are mainly symptomatic and inadequate since none results in restoration of fully functional cartilage. Hyaluronic Acid (HA) intra-articular injections are widely accepted for the treatment of pain associated to OA. The goal of HA viscosupplementation is to reduce pain and improve viscoelasticity of synovial fluid. Platelet-rich plasma (PRP) has been also employed to treat OA to possibly induce cartilage regeneration. The combination of HA and PRP could supply many advantages for tissue repair. Indeed, it conjugates HA viscosupplementation with PRP regenerative properties. The aim of this study was to evaluate the rheological and biological properties of different HA compositions in combination with PRP in order to identify (i) the viscoelastic features of the HA-PRP blends, (ii) their biological effect on osteoarthritic chondrocytes and (iii) HA formulations suitable for use in combination with PRP. HA/PRP blends have been obtained mixing human PRP and three different HA at different concentrations: 1) Sinovial, 0.8% (SN); 2) Sinovial Forte 1.6% (SF); 3) Sinovial HL 3.2% (HL); 4) Hyalubrix 1.5% (HX). Combinations of phosphate buffered saline (PBS) and the four HA types were used as control. Rheological measurements were performed on an Anton PaarMCR-302 rheometer. Amplitude sweep, frequency sweep and rotational measurements were performed and viscoelastic properties were evaluated. The rheological data were validated performing the tests in presence of Bovine Serum Albumin (BSA) up to ultra-physiological concentration (7%). Primary osteoarthritic chondrocytes were cultured in vitro with the HA and PRP blends in the culture medium for one week. Cell viability, proliferation and glycosaminoglycan (GAG) content were assessed. PRP addition to HA leads to a decrease of viscoelastic shear moduli and increase of the crossover point, due to a pure dilution effect. For viscosupplements with HA concentration below 1% the viscoelasticity is mostly lost. Results were validated also in presence of proteins, which in synovial fluid are more abundant than HA. Chondrocytes proliferated overtime in all different culture conditions. The proliferation rate was higher in chondrocytes cultured in the media containing PRP compared to the cultures with different HA alone. GAG content was significantly higher in chondrocytes cultured in PRP and HL blend. We investigated the rheological and biological properties of four different HA concentrations when combined with PRP giving insights on viscoelastic and biological properties of a promising approach for future OA therapy. Our data demonstrate that PRP addition is not detrimental to the viscosupplementation effect of HA. Viscosupplements containing low HA concentration are not indicated for combination with PRP, as the viscoelastic properties are lost. Although having the same rheological behavior of SF and HX, HL was superior in stimulating extracellular matrix production in vitro.